Kelompok Usaha Masyarakat Desa Batang Kuis Pekan Kecamatan Batang Kuis Bidang Kerajinan, Souvenir, Sablon Dan Percetakan Kabupaten Deli Serdang TA. 2024 - Mamed Rofendi Manalu; Monang Juanda Tua Sihombing; Kristian Siregar; RL. Harmadi Tamba; Riswan Limbong; Edward Robinson Siagian; Abdul Sani Sembiring; Elvitrianim Purba (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the skills and competitiveness of community business groups in Batang Kuis Pekan Village in the fields of handicrafts, souvenirs, screen printing, and printing. The methods used include problem identification, program planning, activity implementation, and monitoring and evaluation. The program includes design and production training, digital marketing, and business financial management. The results of the evaluation showed that more than 80% of the participants were able to apply the skills taught, including the use of digital technology for marketing and financial records. The assistance provided also helped participants overcome technical obstacles in production and business management. This activity was strengthened by a discussion session with STMIK lecturer Mulia Darma who emphasized the importance of collaboration between academics, the government, and the business community in building a sustainable business ecosystem. The recommendation for the formation of a local entrepreneurial community is expected to strengthen the network between business actors and support the sustainability of the program. Thus, this program has succeeded in providing real benefits for community business groups and can be used as a model for community-based economic development in other regions.